Patient – practitioner communication and contact lens compliance during a prolonged COVID-19 lockdown. Issue 6 (December 2021) - Cardona, Genis; Alonso, Silvia; Busquets, Anna
Highlights: Compliance with handwashing and contact lens storage case hygiene was low during the 3-months COVID-19 lockdown in Spain. Patient-practitioner communication was common during lockdown. However, communications failed to provide easy-to-follow precise instructions on handwashing and storage case hygiene. Abstract: Purpose: Ocular manifestations and ocular transmission of SARS-CoV-2 in contact lens (CL) wearers may be fostered by non-compliance with care and maintenance instructions which, in turn, may be aggravated by inadequate patient-practitioner communication. The purpose of this research was to determine CL use, compliance and patient-practitioner communication during a 3-month long COVID-19 lockdown in Spain. Methods: An online survey (developed using Google Forms) retrospectively evaluated CL compliance during the 3-month lockdown (responses captured between 15th July and 10th August, 2020), with particular emphasis on patient-practitioner communication, handwashing practices and CL case hygiene and replacement. Results: A total of 247 responses were collected and analysed. Most participants used monthly replacement soft lenses (64.8 %) and multipurpose solutions (75.7 %), with 86.6 % of them owning a storage case for their lenses. During lockdown, a significant percentage of participants ceased lens wear (28.4 %) or reduced wearing time (49.2 %). Regarding patient-practitioner communication, 54.3 % of respondents received specific instructions, mostly about handwashing (93.3 %) and storage case hygiene (48.5 %). The most frequent non-compliant practices were inadequate handwashing (36.4 %), and overextending monthly or two-weekly replacement lenses (35.2 %). Many respondents never cleaned (23.0 %) nor replaced (16.3 %) their storage case, and 27.8 % of them reported not having been informed about case hygiene by their practitioners. Conclusion: Contact lens compliance, particularly in terms of handwashing and storage case hygiene, was poor during a prolonged COVID-19 lockdown, thus stressing the need to foster patient-practitioner communication strategies to curtail the possibility of ocular transmission and the risk of virus tropism.